ETHICAL ISSUES IN ISLAMIC PHILOSOPHY - J. J. Badalova (American Journals Publishing, 2023)
Islamic ethics are discussed in this study from a definitional and academic standpoint. It emphasizes the necessity for Islamic ethics to be systematically relevant to modern situations, which calls for the growth of Islamic ethics as a full discipline capable of handling all obstacles, including conceptual, practical, normative, and applicative ones. According to the researcher, a proper ethics definition should cover habits, character traits, and morally significant conduct. Islamic ethics should effectively handle metaethical, normative, and practical aspects of the topic as a field of study of utmost practical importance.
Keywords: Islamic ethics, Qur'an, Ethics, virtue, adab, philosophy.